Education for flourishing: an illustration of boundary object use, peer feedback and distance learning. Issue 4 (7th May 2020) - Ostuzzi, Francesca; Hoveskog, Maya
Abstract : Purpose: Teaching sustainable development at the higher education level requires that existing curricula are supplemented with multi-disciplinary (and sometimes multi-national) collaboration and integrated thinking. The purpose of this paper is to increase the understanding of a particular framework for business model innovation for sustainability-as-flourishing that is used as a boundary object in the context of interdisciplinary, peer-assessed distance learning. This study is positioned in the broader picture of enlarging curricular content so as to reflect the systemic and interconnected nature of socio-technical and economic developments. The motivation behind this study is the authors' wish to achieve a deeper understanding of how students engage with the complex concept of sustainable business modelling, while using the flourishing business canvas (FBC). Design/methodology/approach: An experiment was conducted on the use of the FBC as a boundary object among 52 engineering students at two universities. Data were provided by the following: iterations of the FBC; oral and written peer feedback; and an online survey. Findings: Based on an evaluation of the experiment, this study shows that the FBC supports the use of multi-disciplinary, multi-national peer and distance learning in sustainability education. Research limitations/implications: This study used one test condition of multi-disciplinary, multi-national collaboration for peer and distance learning at one point in time. Additional tests, using the tools and approaches of this study, are needed. Originality/value: Various tools and methods for use in education have been developed that support a new view of sustainability –sustainability-as-flourishing. Extant research focusses primarily on the development of tools and methods in this area. Not enough attention has been paid to the analysis of their implementation and use in higher education. This paper seeks to fill that research gap.